Characterisation and Properties of Fluorinated Acrylic Latex Prepared with Mixed Surfactants of Sds and Apg. Issue 2 (May 2014) - Jiang, Wei; Li, Wen; Chen, Lijun
The nonionic emulsifier of OP-10 is often used in preparing the latex. OP-10 belongs to a type of NPEOs. However, NPEOs are bioaccumulative and persistent in the environment while nonylphenol, the breakdown product of NPEs, is an endocrine disruptor. Therefore, the EU Commission has recommended implementing a risk reduction strategy, which foresees the ban of all applications leading to direct emissions to waste water and strict emission controls for all other technical processes using NPEOs as surfactants. The aim of the research is to study the possibility that OP-10 is replaced by APG to prepare the fluorinated acrylic latex. The fluorinated acrylic latex was prepared successfully via semicontinuous seeded emulsion polymerization of butyl acrylate (BA), methyl methacrylate (MMA) and hexafluorobutyl methacrylate(HFMA) in water phase initiated with potassium persulfate (KPS) and emulsified with the aid of mixed surfactants of sodium dodecyl sulfonate (SDS) and alkyl polyglucosides (APG). The structure of the resultant latex is confirmed by Fourier transform infrared spectroscopy (FTIR) spectrum. The influences of the amount of APG on the properties of the resultant latex and its film were investigated in detail. Results show that the particle size is decreased with the increase amount of APG. However, the calcium ion stability of the latex is increased with the increase of amount of APG.